PROBLEMATIKA PENEGAKAN HUKUM DAN ETIKA PROFESI DI INDONESIA: ANALISIS DENGAN PENDEKATAN NILAI-NILAI AJARAN ISLAM - Hanafi, Suhri (Hunafa: Jurnal Studia Islamika, 2009)
This paper deals with the enforcement of the law and the ethical codes of legal profession, with an analysis from the Islamic approach. It explores legal issues that relate to legal officials, as well as the background and reasons behind the significance of such enforcement that is based on Islamic piety (taqwÃ¢). This paper concludes that the enforcement of the ethical code of legal profession, which is based on Islamic piety, is a solution for the law enforcement and the establishment of the supremacy of law in society as well.Kata Kunci: penegakan hukum, norma hukum, etika profesi, ajaran Islam